Association between nursing care performance with perception of financial rewards, career development and supervision - Ayu Ratih Cempakasari; Ni Made Sri Nopiyani; Dyah Pradnyaparamitha Duarsa (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: The performance of nurses in providing care to patients is an important component for patient satisfaction and healing. Nurse's performance is determined by many factors. This study aims to determine the association between nurse performance in providing nursing care with education, nurse perceptions of financial rewards, career development opportunities, and supervision of the ward head. Methods: A cross-sectional survey was conducted on all nurses (164 people) at inpatient wards of Tabanan General Hospital. Data collection was carried out using a self-administered questionnaire in April 2018. Bivariate analysis was performed using chi-square test, and multivariate analysis was conducted using multiple logistic regression to determine the adjusted odds ratios. Results: The results showed that the mean score of nursing care performance was 70.17 from a maximum score of 80. All independent variables were found to be associated with nurse performance, namely perceptions of career development opportunities (AOR=1.6; 95%CI: 1.03-1.3; p=0.01), financial rewards (AOR=1.1; 95%CI: 1.01-1.2; p=0.03) and supervision of the ward chief (AOR=1.1; 95%CI: 1.01-1.2; p=0.02). Conclusion: Nurses' perceptions of financial rewards, career development opportunities, and supervision of the ward chief are associated with nursing care performance. Provision of rewards, career development and supervision need to be considered in the efforts to improve nurse performance.